The epistemological model of disability, and its role in understanding passive exclusion in eighteenth and nineteenth century Protestant educational asylums in the USA and Britain - Hayhoe, Simon (International journal of Christianity & education, 2016)
This article examines how the process of constructing knowledge on impairment has affected the institutional construction of an ethic of disability. Its primary finding is that the process of creating knowledge in a number of historical contexts was influenced by traditions and the biases of philosophers and educators. This process was in order to signify moral and intellectual superiority, rather than a desire to improve the lives of disabled people through education. The article illustrates this epistemological process in a case study of the development of Protestant asylums in the latter years of the nineteenth century.